Profile of candidates for the transplant waiting list of deceased kidney donor at a center providing renal replacement therapy in Brazil - Pereira, André Barreto; Penido, Maria Goretti Moreira Guimarães; Campos Neto, Milton Soares; Silva, Gustavo Mário Capanema (Brazilian Journal of Transplantation, 2005)
Introduction: The literature records no consensus as to the indications and counter-indications to the inclusion on the waiting list for deceased kidney donor transplantation in the replacement renal therapy center. Objectives: To assess the demographic profile, causes indicating the inclusion or not on that transplantation list, and the primary disease of patients under replacement renal therapy in that center. Methods: It was analyzed the database of patients under replacement renal therapy as to demographic data, primary disease and indication and counter-indications to the inclusion on the renal transplantation of deceased donor. Groups were divided in: G1 (Able to Transplantation), G2 (Unable to transplant), G3 (Assessment). Results: from 408 patients, G1 had 127 male patients (54%): mean age of 43 years (15-65), 41% with chronic glomerulonephritis, 12% hypertensive nephrosclerosis, 10% chronic interstitial tubulus nephritis, 6% diabetes mellitus, 6% reflux nephropathy. G2 had 166 patients: 46% male (mean age: 62 years [25-88]), 30% had diabetes mellitus, 15% chronic glomerulonephritis, 14% hypertensive nephrosclerosis, 11% atheroembolic disease. G3 had 115 patients: 62% male (mean age of 49 years (16-65), 42% with diabetes mellitus, 4% atheroembolic disease, and 48% needing cardiologic assessment. The major reasons to the inclusion in the G2 group were: age higher than 65 years and refusal to the transplantation. Conclusions: a percentage expected in that center was able to be included on the waiting list of deceased kidney donor (31%), and the higher counter-indications were advanced age and refusal.